DIAGNOSIS IN AYURVEDA WITH SPECIAL REFERENCE TO TRIVIDHA BODHYA SAMGRAHA - Monika Gupta,; Gopikrishna, (International Journal of Ayurveda and Pharma Research, 2020)
Ayurveda is comprehensive in its approach which emphasizes naming a disease is not necessary rather knowledge about Nidana (Etiological Factors), Dosha, Dushya and Samprapti of disease (Pathology) are crucial. Several diseases mentioned in the Samhitas (Classical texts) does not match with clinical presentation of disease thus in order to ascertain a working diagnosis clinical history and detailed physical examination are critical to the diagnostic process. Based on the ‘Purush Purush Veekshya Nyaya’, various Siddhantas (principles) ought to be adopted to diagnose the disease, as diagnosis is always individual to each patient. Acharya Charaka has mentioned the concept of Trividha Bodhya Samgraha (Vikara Samuthana, Vikara Adhishtana and Vikara Prakruti Vishesha that deals with the principles of etiology and different stages of pathology of a disease. This concept holds basis for Ukta Gada (listed diseases) as well as for Anukta Gada (unlisted diseases). Thus it can be applied to diagnose any of the disease. If accurate diagnosis is made in proper and sequential manner it provides the best outcome by assessing the response to multimodal approach of Ayurveda through treatment modality. This present article aims to provide an insight to develop a clinical approach to Ayurveda diagnosis enunciated in Samhitas in context of Trividha Bodhya Samgraha underneath the spectrum of Anukta Vyadhi.